Annealing effect on ultraviolet sensor performance with porous silicon based - Muhammad Zuhdi, Mohd Yusoff; Rozina, Abdul Rani; Irnie Azlin, Zakaria; Siti Rabizah, Makhsin; Ahmad Sabirin, Zoolfakar; Zainah, Md Zain; Nur Lili Suraya, Ngadiman (Institute of Electrical and Electronics Engineers Inc., 2022)
Nowadays, most semiconductor industries apply silicon-based material in developing advanced electronic device. Concerns with heat management of electronic devices which getting worst day by day, the nanostructures technologies were introduced in order to overcome the problem. The nanostructures development on bulk crystalline silicon known as porous silicon which could be produced via anodization method. In this study, the anodized porous silicon was annealed at temperatures of 200°C up to 800°C for the research purpose of annealing effect on ultraviolet sensor performance. The structures of porous silicon were analyzed via FESEM and XRD characterization in order to identify the morphology and crystallinity of porous silicon. Then, the ultraviolet sensors were produced and the sensors performance were analyzed. After post-annealing treatment, the anodized porous silicon has the strongest crystalline peak at 600°C and 800°C, while below 400°C, the porous silicon samples have a broadened XRD peak around 2 θ=33°. However, our experimental results show that an ultraviolet sensor which anneal at temperature 200°C have the best sensing performance.